Effects of the hangover secret on mitigating hangover symptoms: A pilot study. Issue 3 (16th July 2021) - Wang, Der Yu; Patel, Sheel; Maiton, Kimberly; Pham, Kevin; O'Dell, Kate M.; Nguyen, Nancy N.; Shah, Sachin A.
Abstract: Background: Due to the popularity of excessive alcohol consumption, there is an increasing need for hangover symptom remedies. Most commercially available hangover treatment products have not been tested for efficacy through clinical study. Aims: The purpose of this pilot study was to characterize the activity of a commercially available hangover product, The Hangover Secret (THS). Methods: This was a randomized, double‐blinded, placebo‐controlled, crossover pilot study. Healthy volunteers of 21‐ to 40‐years‐old were eligible for participation, and received either THS or placebo on two different occasions. Participants were given 43 mL of whiskey every twenty minutes for up to 3 hours to achieve a blood alcohol concentration (BrAC) ≥ 0.12%. Hangover severity was assessed using the Acute Hangover Scale (AHS) and Acute Hangover Severity Scale (AHSS) validated tools. Results: Nine participants completed the study. AHS scores increased from baseline to 7 AM by 4.11 ± 3.17 and 1.26 ± 2.29 for the placebo and active arms respectively ( P = .16). AHS headache scores increased from baseline to 7 AM by 2.44 ± 1.67 and 1.11 ± 1.17 for the placebo and active arms respectively ( P = .06). AHSS scores increased from baseline to 7 AM by 1.0 ± 1.05 and 0.41 ± 1.08, for the placebo and active arms respectively ( P = .30). There was no significant difference between average BrAC at 7 AM between the placebo and active arms. Conclusion: THS showed positive signals in the prevention of alcohol‐induced hangover, especially headaches. The improvements with THS surpassed the minimum clinically important difference in overall AHS score and three individual AHS symptoms scores (hangover, headache, and thirsty). THS's reduction in AHS or AHSS scores did not reach statistical significance likely due to the small sample size. Larger studies with appropriate sample sizes are needed in light of these promising findings.